2022
DOI: 10.1088/1748-9326/ac740b
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal patterns of oasis dynamics in China’s drylands between 1987 and 2017

Abstract: Oases are among the most productive and vulnerable ecosystems on drylands as well as central areas of human life and economic development. In China, oasis expansion and degradation are directly related to the survival and development of tens of millions of inhabitants who live within them, profoundly affecting human well-being. However, our understanding of the spatiotemporal dynamics of China’s oases has been limited. This creates a challenge to accurately assess the environmental impacts of oasis dynamics an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 57 publications
3
12
0
Order By: Relevance
“…Most of these counties are located in the Kubuqi Desert, the Hexi Corridor, the northern foothills of the Tianshan Mountains, and the Aksu River and Tarim Main River regions. Moreover, some of these counties have suffered from water shortages, as also evidenced by previous observations (e.g., soil drying and groundwater depletion in some oasis areas) (P. Chen et al., 2022b; Xie et al., 2014; J. Yao et al., 2022). Although total water availability at the oasis scale still has capacity for use, the monthly water deficit has experienced an increasing trend at the county scale.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Most of these counties are located in the Kubuqi Desert, the Hexi Corridor, the northern foothills of the Tianshan Mountains, and the Aksu River and Tarim Main River regions. Moreover, some of these counties have suffered from water shortages, as also evidenced by previous observations (e.g., soil drying and groundwater depletion in some oasis areas) (P. Chen et al., 2022b; Xie et al., 2014; J. Yao et al., 2022). Although total water availability at the oasis scale still has capacity for use, the monthly water deficit has experienced an increasing trend at the county scale.…”
Section: Discussionsupporting
confidence: 59%
“…Previous studies of hydrological processes in oases have reported that oasis expansion intensifies regional evapotranspiration (Y. Zhou et al., 2018), and that rapid revegetation and reclamation of land for cropland by irrigation have caused some oases in the Kubuqi desert (P. Chen et al., 2022b), WeiGan–KuChe River basin (Maihemuti et al., 2021), Manas River basin (Yang et al., 2019; Q. Zhang et al., 2012), and Heihe River basin (Z. Lu et al., 2015) to experience soil desiccation and groundwater overdraw. However, these studies mainly analyzed relationships between oasis dynamics and evapotranspiration and soil moisture, or used observational data and model simulations to estimate watershed‐scale water dynamics (Maihemuti et al., 2021; D. Zhou et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantitative assessment of the interannual variability in grassland landscape patterns in response to their ecosystem service values is a current research hot spot [ 107 ]. Monitoring the spatial and temporal dynamics of grassland areas can help decision makers to plan the use of grassland in a rational manner and achieve the sustainable development of grassland [ 108 ]. Landscape changes directly affect changes in the demand and supply of ecosystem services.…”
Section: Resultsmentioning
confidence: 99%
“…Li et al, 2016). Grassland, as the primary component of oases, plays a vital role in preventing desert encroachment and maintaining oasis stability, in addition to providing a wide range of ecosystem services (Chen et al, 2022;Ge et al, 2022; K. Zhang et al, 2017). In China, oasis grasslands are threatened by the expansion of cropland.…”
Section: Introductionmentioning
confidence: 99%